Authentic Assessment: Portfolio-Based Assessment in Literacy Learning in Indonesian Schools - Abdul Haliq; Sakaria Sakaria (Fakultas Sastra - Universitas Muslim Indonesia, 2019)
Comprehensive evaluation and emphasis on the student activity process as well as providing broad wiggle room for students is needed in learning assessment. Literacy assessment with such a model is necessary to improve students' literacy skills. One assessment model that puts pressure on student activity and provides ample space for everyone to respond to an assignment in its own way is the assessment of portfolio. This paper aims to explore portfolio assessments as part of an authentic assessment for use in literacy assessments. This research uses literart research study method to provide an overview of the use of portfolios in literacy assessments in Indonesian schools. Portfolio assessment on students’ literacy skills is carried out through Indonesian language learning, especially on the efficacy of writing. The portfolio assessment adopted uses models offered by Hamp-Lyons and Condon (2000) consisting of collection, selection, and reflection. Assessments are carried out by combining formative and summative assessments. To balance the summative aspects of portfolio assessment, several formative strategies can be adopted (Lee & Lam, 2009), including (1) ongoing teacher feedback, (2) conferences, and (3) peer reviews.